2013
DOI: 10.1089/tmj.2012.0260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Skin Cancer in Northern California Kaiser Permanente's Store-and-Forward Teledermatology Referral Program

Abstract: The use of teledermatology in remote areas results in a shorter time to biopsy than traditional referral methods as a result of improved triaging measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 12 publications
2
16
0
2
Order By: Relevance
“…However, this difference was not statistically significant, and a larger sample size would be beneficial in clarifying the significance of this trend. The observed keratinocytic carcinoma detection rates for SAF teledermatology and F2F consultation in this study (5.5% and 8.5%, respectively) are comparable to prior studies in the VA and general population …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, this difference was not statistically significant, and a larger sample size would be beneficial in clarifying the significance of this trend. The observed keratinocytic carcinoma detection rates for SAF teledermatology and F2F consultation in this study (5.5% and 8.5%, respectively) are comparable to prior studies in the VA and general population …”
Section: Discussionsupporting
confidence: 88%
“…The observed keratinocytic carcinoma detection rates for SAF teledermatology and F2F consultation in this study (5.5% and 8.5%, respectively) are comparable to prior studies in the VA and general population. 5,11,12 Our study focused on the prevalence of major skin cancer risk factors such as personal and family history of skin cancer and history of immunosuppression as these are queried on the standardized teledermatology intake form and routinely in clinic visits. Information such as Fitzpatrick phototype, history of sunburn, or atypical mole history were not available for any SAF teledermatology patients unless they were seen in dermatology clinic subsequently.…”
Section: Limitationsmentioning
confidence: 99%
“…In measures of its reach, we estimated that 975,000 patients in the Champlain LHIN are enrolled with a PCP who uses eConsult, and that 61% of enrolled PCPs are active users (ie, have submitted a case in the past 12 months). These figures align with other services reported in the literature: the Kaiser Permanente Network serves half a million patients in its Colorado location 6 and over 3 million in California 43 , and a teledermatology service in the Netherlands identified 65% of PCPs as active users (ie, those who had completed at least one case) who submitted an average of 9.1 cases per year. 44 We also found that in a small percentage of cases (3.4%), PCPs did not originally intend to refer the patient, but ultimately chose to do so based on the advice they received.…”
Section: Discussionsupporting
confidence: 83%
“…In France, as in some other countries (i.e., the United States of America, Australia and Switzerland), access to dermatologists is limited by an undersupply of these specialists, which results in long wait times. In rural areas, this problem is more acute because of both the rarity of specialists and geographical distances …”
Section: Introductionmentioning
confidence: 99%
“…In rural areas, this problem is more acute because of both the rarity of specialists and geographical distances. [12][13][14] The Agricultural Social Insurance Mutual Benefit Fund (MSA) includes in its mission the prevention of occupational and nonoccupational health risks. In 2014, the MSA offered to its customers who worked in agriculture and lived in rural area with reduced access to dermatologists the ability to participate in a 1-day teledermoscopic (TDS) screening event that was jointly organized by the MSA and the Union of Dermatologists [i.e., the Syndicat national des dermatologues-v en er eologues (SNDV)] for a national skin cancer screening day.…”
Section: Introductionmentioning
confidence: 99%